UJI FITOKIMIA DAN TOKSISITAS EKSTRAK METANOL JARINGAN KULIT BATANG TANAMAN BINTARO (Cerbera manghas L) TERHADAP BIBIT IKAN NILA (Oreochromis niloticus) - Abunoya, Juleha Ilfri; Usman, Usman (PROSIDING SEMINAR KIMIA, 2024)
The Bintaro tree (Cerbera manghas L) is a mangrove plant native to the tropics of Indonesia, Australia, Madagascar, and the western islands of the Pacific Ocean. The name Cerbera comes from the serberine poison found in the seeds and all parts of the tree. The bark contains saponins and tannins, and the leaves and fruits contain polyphenols. The purpose of this study was to determine the content of active compounds from the bark tissue of bintaro plants and the results of toxicity tests of bintaro plant stem tissue against tilapia. The method used in this study consists of 3 stages, namely extraction, phytochemical test (color test) and toxicity test. Extraction was done by maceration method using methanol solvent. Phytochemical test was done by color test. Phytochemical test results showed that methanol extract of bintaro stem bark was positive for alkaloid, steroid and triterpenoid secondary metabolites. The toxicity test of bintaro bark extract on tilapia fish seeds using the calculation of LC50 obtained a result of 88.1198 Based on the results of the phytochemical test of methanol extract of bintaro bark tissue (Cerbera manghas L), it is concluded that the methanol extract clearly contains alkaloid, steroid, and triterpenoid compounds, and the toxicity test of methanol extract of bintaro bark tissue on tilapia fish seeds using the BSLT method shows the toxic activity of methanol extract of bark tissue is toxic. Keywords : Cerbera Manghas L., Bintaro, Phytochemical Test, Toxicity Test